The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000489802
|View full text |Cite
|
Sign up to set email alerts
|

A functional Variant (Rs35592567) in TP63 at 3q28 is Associated with Gastric Cancer Risk via Modifying its Regulation by MicroRNA-140

Abstract: Background/Aims: TP63 was believed to play an important role in the development of many malignancies, while the polymorphisms located at the miRNA binding sites within the 3’UTR of TP63 mRNA may interfere with its expression. In this study, we aimed to study the role of TP63 regulation in the tumorigenesis of gastric cancer (GC). Methods: Computational and luciferase analysis were used to search and confirm the target of miR-140. Real-time PCR, western-blot, MTT assay, and flow cytometry cell cycle analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another cytoband 3q28 in SCC has been reported in previous study (Bodelon et al 2016 ). In 3q28, mutations in TP63, a member of the p53 family, are associated with various cancers: notably, lung and bladder cancers (Lu et al 2018 ; Wang et al 2016 ). Min Liu hypothesized that highly expressed HPV-human fusion transcripts could promote overexpression of E6*I and E7 and inhibit the transcription of tumor suppressor genes TP63 and P3H2 (Liu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another cytoband 3q28 in SCC has been reported in previous study (Bodelon et al 2016 ). In 3q28, mutations in TP63, a member of the p53 family, are associated with various cancers: notably, lung and bladder cancers (Lu et al 2018 ; Wang et al 2016 ). Min Liu hypothesized that highly expressed HPV-human fusion transcripts could promote overexpression of E6*I and E7 and inhibit the transcription of tumor suppressor genes TP63 and P3H2 (Liu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the other two genes, HDAC10 and TP63, for which no over-representation of (predicted) damaging variants was identified in CRC patients compared to controls, no previous studies have identified an association with CRC predisposition. TP63 alleles have been associated with susceptibility to different cancer types, but not to CRC (some examples: [49][50][51][52][53]). Somatic mutations in HDAC10 and TP63 occur in 1.1% and 2.4% of CRCs respectively (source: cBioPortal; accessed Jan 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence identified that SNP mutations in lncRNAs may alter their structural stability, generate alternative splicing, impair the translation of target mRNAs, and ultimately affect the risk of various cancers [ 6 ]. For example, rs35592567 polymorphism affect the expression of TP63 by interfering miR-140, which may serve as a reasonable explanation for the increased susceptibility of gastric cancer [ 46 ]. Additionally, Xue et al reported that rs7958904 G > C strikingly altered the secondary structure of HOTAIR, suggesting the SNPs affect the susceptibility to colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%